Power Data Collection Terminal Protection Based On SM9 - Piao, Liu; NuanQiang, Ye; HanXian, Han; Man, Luo Jin; ShuFeng, Yang; RuiJue, Feng; MengZhen, Song (Proceedings (International Conference on Power System Technology. Online), 2021)
With the proposal of the development plan of the Power and Internet of things, the power data collection terminal has received strong attention. However, due to the low security of the terminal and the existence of security vulnerabilities, it is easy to become a hacker attack on the power network media. To protect the information security of power data collection terminal, an identification-based SM9 cipher algorithm is adopted. By analyzing the characteristics of asymmetric encryption algorithm, studying the operation of equipment on a power data collection terminal, the national secret algorithm SM9 encryption and decryption process and different plaintext and length of the test, the protection of information security of the terminal system is realized.